Impact of Temperature on Groundwater Source Attenuation Rates at Hydrocarbon Sites. Issue 3 (19th July 2017) - Kulkarni, Poonam R.; King, David C.; McHugh, Thomas E.; Adamson, David T.; Newell, Charles J.
Abstract: The temperature sensitivity of microbial populations is reflected in measured source attenuation rates at hydrocarbon‐impacted sites. The objective of this study was to evaluate the correlation between temperature and source attenuation rates (concentration vs. time attenuation rate over many years) of benzene and toluene by analyzing groundwater monitoring data from >2000 hydrocarbon sites. Historical monitoring records were obtained from three databases, processed to yield long‐term multiyear source attenuation rates, and then compared with representative temperatures at each site. Statistically significant and positive relationships between temperature and source attenuation rates were established for benzene and toluene, indicating that temperature does impact hydrocarbon degradation, but is one of many factors that contribute to source attenuation. There was an observed 1.1 to 1.6 times increase in attenuation rates per 10 °C increase in temperature, which is less than the rate increases predicted by the Arrhenius equation. The temperature dependence on attenuation rate is consistent with several lines of evidence that methanogenesis plays a key role in the rate of hydrocarbon source zone attenuation rather than being controlled strictly by the availability of electron acceptors. First, methanogenesis is known to be strongly influenced by temperature, with significantly higher rates up to about 35 °C. Second, the temperature‐degradation rate relationship was stronger at sites with deeper water tables (>30 ft) that are less susceptible to oxygen influx than sites with shallow water tables (<15 ft). Third, dissolved methane concentrations were higher at sites with warmer temperatures. Overall, these results provide indirect support for a conceptual model where methanogenesis is a key degradation process at hydrocarbon sites, and that attenuation of these source zones is temperature‐sensitive.